A Wideband Printed Directional Antenna Array with Impedance Regulating Load - Chun-Ying Kang; Shu Lin; Li-Wen Jing; Yu Tian; Jia-Xin Dong; Jia Lu (International Journal of Antennas and Propagation)
We proposed a broadband directional antenna array working at mobile communication frequency band, which achieves a relative bandwidth of 50.7%. This binary antenna array is fed by two branches of the balanced microstrip. To enhance the antenna bandwidth, we introduced a section of loading metal strip. The antenna prototype has a S11 lower than −10 dB within the 1.5 GHz to 2.52 GHz frequency band, particularly from 2.01 GHz to 2.50 GHz, the S11 is lower than −15 dB. The gain varies with relatively small variation within the working band, which is 5.4 dBi to 8.7 dBi.